Hepatocellular Carcinoma in Liver Cirrhosis: Surgical Resection versus Transarterial Chemoembolization—A Meta-Analysis - Teodor Kapitanov; Ulf P. Neumann; Maximilian Schmeding (Gastroenterology Research and Practice)
We compare the value of TACE to liver resection for patients with BCLC stage A and B HCC. For patients with HCC in cirrhosis LT is the treatment of choice. TACE represents the current standard for unresectable BCLC stage B patients not eligible for LT. Recently liver resection for HCC and significant cirrhosis has become increasingly popular. A systematic search of the literature and meta-analysis was conducted to identify studies, reporting short- and long-term results of hepatic resection versus TACE for HCC treatment. The data were analyzed regarding the odds for 30-day mortality and hazard ratio for overall-survival. 12 studies comparing short- and long-term outcome of HR versus TACE for HCC were identified. Peri-interventional mortality and overall survival were investigated. Peri-interventional mortality was higher for surgical resection (n.s.), and overall-survival was significantly better for surgically treated patients at one year (P=0.002) and 3 years (P≤0.00001). The hazard ratio of overall-survival for all twelve studies was 0.70 (P=0.0001) and significantly in favor of surgical treatment. Although large RCTs are missing and the available data are limited and not homogeneous a reappraisal of the current treatment guidelines should be considered based on the superior long-term outcome for surgically treated patients.